PERAN PARTAI GOLONGAN KARYA DALAM MELAKSANAKAN PENDIDIKAN POLITIK - M Triyastono Taufik; Ujang Jamaludin; Ronni Juwandi (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2019)
This studies aim to get knowing that . The Role of Golongan Karya Political Party in The Political Education Implementation. This research held for four month start from December until April 2019. Used on the descriptive method with qualitative approach, data are collected use with interview, observation, and documentation, analysis data collected are following presented taking data, data reduction, data presentation and withdrawal data. Research result indicate theres a trouble from Golongan Karya Political Party (Golkar) in Political Education implementation to society. Political Education implementation do with various methode, theres with visit society door-to-door, sosialization, workshop. Based on research result concluding that an Implementation of Political Education by Golongan Karya Political Party (Golkar) Serang City means to society reinforcement and enhancement quality in order to be political invidual capable.